Effect of increased copper ion content in the medium on the regeneration of androgenetic embryos of carrot (Daucus carota L.) - Urszula Kowalska; Katarzyna Szafrańska; Dorota Krzyżanowska; Waldemar Kiszczak; Ryszard Górecki; Krystyna Janas; Krystyna Górecka (Acta Agrobotanica, 2012)
The study was conducted to determine the effect of elevated concentrations of copper in the medium on the regeneration of androgenetic embryos of the carrot cultivar ‘Kazan F1’ obtained in anther cultures and to determine the level of soluble phenols produced in the regenerates under copper stress. Green embryos were laid out on 4 regeneration media based on B5 medium (G a m b o r g et al. 1968) without hormones, containing 0.1 – control, 1, 10, and 100 μM CuSO4×5H2O. The plant material was passaged 3 times, after 4, 9 and 15 weeks. During these passages the emerging structures were examined; they were classified in terms of growth and development in vitro, weighed and counted. The levels of soluble phenols in the freeze-dried regenerates were determined. The elevated concentrations of copper in the regeneration media affected positively the formation of complete plants (rooted rosettes) and secondary embryos during the first 4 weeks of culture. After a longer regeneration time (9, 15 weeks), the elevated concentrations of copper caused negative effects: deformation of rosettes. After 15 weeks, the number of rooted rosettes decreased. The 9-week culture subjected to copper stress brought about an increase in the amounts of soluble phenols. The highest values were recorded in the rosettes treated with 10 μM CuSO4. Prolonged exposure to media containing elevated concentrations of CuSO4 caused a reduction in the accumulation of phenolic compounds in the rosettes.